Throughput improvement for delay-sensitive video broadcast in wireless mesh networks. (November 2015) - Chang, Yanan; Jia, Xiaohua; Cui, Jianqun
Graphical abstract: Highlights: We formulate the problem as a mixed integer quadratically constrained program. We use a three-step method to build a broadcast tree and schedule transmissions. We show the effectiveness of our method by simulation. Abstract: In this paper, we address the problem of broadcast routing and scheduling of video streaming for delay-sensitive applications in backbone wireless mesh networks. Given a source node and a set of destinations, we aim to build a broadcast tree and compute an optimal schedule such that the throughput for the source to broadcast streaming data to all the destinations is maximized. We divide the whole period for video broadcast into identical time frames and prove that maximizing the throughput can be converted into minimizing the length of a time frame. We propose a three-step method as a solution. Firstly, we build the broadcast tree by defining a new routing metric to select relay nodes. Then we use local search method to adjust the tree structure. Last, we propose a greedy method to schedule concurrent transmissions. Simulations have demonstrated that our method can improve the performance significantly compared with existing methods.